2023
DOI: 10.1371/journal.pmed.1004155
|View full text |Cite
|
Sign up to set email alerts
|

The cost and cost-effectiveness of novel tuberculosis vaccines in low- and middle-income countries: A modeling study

Abstract: Background Tuberculosis (TB) is preventable and curable but eliminating it has proven challenging. Safe and effective TB vaccines that can rapidly reduce disease burden are essential for achieving TB elimination. We assessed future costs, cost-savings, and cost-effectiveness of introducing novel TB vaccines in low- and middle-income countries (LMICs) for a range of product characteristics and delivery strategies. Methods and findings We developed a system of epidemiological and economic models, calibrated to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 27 publications
(42 reference statements)
3
25
0
Order By: Relevance
“…Our analyses demonstrated that both vaccines could be cost-effective, aligning with previous cost-effectiveness analyses of tuberculosis vaccines. 6,29 While vaccination could have a substantial budget impact, costs could be partially offset with diagnostic and treatment savings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses demonstrated that both vaccines could be cost-effective, aligning with previous cost-effectiveness analyses of tuberculosis vaccines. 6,29 While vaccination could have a substantial budget impact, costs could be partially offset with diagnostic and treatment savings.…”
Section: Discussionmentioning
confidence: 99%
“…4 The National Strategic Plan also calls for further development in tuberculosis vaccines, which has been a high priority for global organisations such as the World Health Organization (WHO). A recently completed WHO-commissioned study assessing the full value of tuberculosis vaccines made a strong case from the health and economic perspectives for continued investment, [5][6][7][8][9] and previous work has demonstrated that novel vaccines or vaccination strategies will be needed to eliminate tuberculosis. 10,11 Currently, sixteen candidates are in various phases throughout the vaccine pipeline, being trialled in a variety of ages and spanning prevention of disease, infection, and recurrence endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models have been used extensively to estimate the potential impact and cost-effectiveness of tuberculosis vaccines with different specifications [6]. Models have, for example, provided age indications for TB vaccines, by demonstrating the greater and more rapid impact before 2050 of targeting adolescents and adults instead of infants in low and middle income countries [7], [8], and older adults only in settings such as China [9].…”
Section: Introductionmentioning
confidence: 99%
“…Since the efficacy of new tuberculosis vaccines may depend on the host infection status, self-clearance also has the potential to affect the impact of new vaccines. While a number of more recent vaccine models have included a simple representation of self-clearance ( [6], [8]), none have investigated its effects on vaccine impact, or have explored the effects of the large amounts of uncertainty that exists around the properties of self-clearance. No earlier vaccine models included self-clearance at all ([10], [15]).…”
Section: Introductionmentioning
confidence: 99%
“…The same group also published a cost-effectiveness model for the same LMICs, estimating a saving of US$283 billion to $474 billion by 2050, especially in countries with high tuberculosis burdens. 8 …”
mentioning
confidence: 99%